2011
DOI: 10.1073/pnas.1014293108
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular proton shuttle supports not only catalytic but also noncatalytic function of carbonic anhydrase II

Abstract: Carbonic anhydrases (CAs) catalyze the reversible hydration of CO 2 to HCO 3 − and H + . The rate-limiting step in this reaction is the shuttle of protons between the catalytic center of the enzyme and the bulk solution. In carbonic anhydrase II (CAII), the fastest and most wide-spread isoform, this H + shuttle is facilitated by the side chain of His64, whereas CA isoforms such as carbonic anhydrase III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 50 publications
9
118
0
3
Order By: Relevance
“…In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48). This led to the conclusion that CAII, directly bound to the transporter, can act as a H ϩ -collecting/distributing antenna, which shuttles protons between transporter and surrounding protonatable residues to support proton/lactate cotransport (48). By introduction of single-site mutations in the C terminus of MCT1 and subsequent expression of these mutants in CAII-injected Xenopus oocytes, we could identify the two glutamic acidic residues Glu 489 and Glu…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48). This led to the conclusion that CAII, directly bound to the transporter, can act as a H ϩ -collecting/distributing antenna, which shuttles protons between transporter and surrounding protonatable residues to support proton/lactate cotransport (48). By introduction of single-site mutations in the C terminus of MCT1 and subsequent expression of these mutants in CAII-injected Xenopus oocytes, we could identify the two glutamic acidic residues Glu 489 and Glu…”
mentioning
confidence: 72%
“…39 -41. Using heterologous protein expression in Xenopus oocytes, we have recently reported that CAII enhances transport activity of MCT1 and MCT4, while leaving transport activity of MCT2 unaffected (42)(43)(44)(45)(46). In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48). This led to the conclusion that CAII, directly bound to the transporter, can act as a H ϩ -collecting/distributing antenna, which shuttles protons between transporter and surrounding protonatable residues to support proton/lactate cotransport (48).…”
mentioning
confidence: 75%
“…Thus, our results suggest that CAs, known to be active extracellularly, also display robust intracellular activity. Therefore, the intracellular CA activity, which is crucial for cellular H + dynamics and various acid/base transport processes across the cell membrane (20,26), is not only due to known, soluble cytosolic CAs, but is also attributable to intracellular activity of membrane-associated CAs. This discovery makes it important to take into account the interplay between intracellular and extracellular CA activities to understand their role in physiological processes and to design drugs specific for extracellular CA isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence about the catalytic activity of CA in oocytes, either expressed or injected as protein, can be obtained physiologically by measuring intracellular H + in intact oocytes, and by mass spectrometry of lysed oocytes (20,21). By measuring H + with ion-selective microelectrodes in the cytosol and at the outer membrane surface, intra-and extracellular CA activity can be identified and discriminated by the rate and amplitude, respectively, of H + changes.…”
mentioning
confidence: 99%
“…Since CA inhibitors have been shown to reduce IOP exclusively by lowering the aqueous humour flow and these compounds have been used for the treatment of glaucoma for years 11,12 . The rate-determining step for the CO 2 hydration reaction catalyzed by CAs is the proton transfer reaction from the water bound to the Zn(II) ion to the reaction medium, with generation of the zinc hydroxide species of the enzyme [13][14][15][16][17][18][19][20] . Several anions behave as inhibitors for the CO 2 hydration reaction 21,22 and coordinate directly to Zn(II) ion.…”
Section: Introductionmentioning
confidence: 99%